B cell chronic lymphocytic leukaemia/small lymphocytic lymphoma: role of ZAP70 determination on bone marrow biopsy specimens. Issue 6 (17th August 2006) - Sabattini, Elena; Orduz, Rocio; Campidelli, Cristina; Zinzani, Pier Luigi; Callea, Vincenzo; Zupo, Simona; Cutrona, Giovanna; Morabito, Fortunato; Ferrarini, Manlio; Pileri, Stefano
Abstract : Background: The course of chronic lymphocytic leukaemia/small lymphocytic lymphoma (CLL/SLL) partly depends on the mutational status of the variable region of immunoglobulin heavy chain genes (IgVH ), which defines two subgroups of tumours: mutated and unmutated. The expression of zeta-associated protein 70 (ZAP70) is significantly associated with the more aggressive unmutated forms. Aims: To assess the feasibility of the ZAP70 immunohistochemical test on bone-marrow biopsy (BMB) specimens and to compare the results with those of western blotting (WB) and IgVH mutational status assessed on neoplastic cells from peripheral blood. Methods: 26 patients with CLL/SLL detected on BMB and with known IgVH mutational status were selected. ZAP70 was determined by immunohistochemistry (IHC) comparing three antibodies from different sources (Upstate, Cell Signaling, Santa Cruz, California, USA) and two different methods (APAAP and EnVision + ). In 23 cases, ZAP70 WB results were also available. Results: ZAP70 determination on BMB specimens turned out to be easily feasible with routine procedures with reagents from Upstate and Cell Signaling. The results were concordant with those obtained with WB and mutational status analysis in >80% of the cases with both reagents. Three of four discordant cases were mutated/ZAP70 positive, with two staining weakly for ZAP70 on both WB and IHC. Conclusions: The study confirms the role of ZAP70 as a possible surrogate of mutational status and emphasises its application in routine diagnostics; it discloses a small subset of discordant cases (mutated/ZAP70 weakly positive) that clinically cluster with the more favourable forms.